Relasi Muslim dan Nasrani Terkait Pendirian Gereja di Wilayah Perumahan Non-Dinas TNI Angkatan Laut di Driyorejo Gresik - Kasno Kasno (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article examines the interfaith relation of Muslims and Christians in the process of establishment of churches in Perumahan Non-Dinas TNI Angkatan Laut in Driyorejo Gresik. The article concludes that the real inter-religious relation in Driyorejo is very good. It is characterized by a relationship of mutual respect and tolerance in order to implement the teachings of their respective religions in the area. This relationship functionally indicates that the process of adaptation is very good. The harmony of inter-religious relation contributes to the creation of an orderly and safe society. Social-religious elements can be integrated together to create a solid and unified society. The harmony can be achieved because their religious and cultural values of society emphasize the accommodation and tolerant attitude. The social problems associated with the establishment of churches in the Perumahan indeed could lead to social unrest. Borrowing structural-functionalist theory, it can be stated that systemic balance is likely to change because of the influence of extra system. The public unrest indicates that the system is experiencing instability. However, the social system has an internal control mechanism that can stabilize the system after disorder. In the case of the establishment of churches, the community tend to choose legal approach as a means of controlling or resolving conflict.